2014
DOI: 10.1016/j.cocis.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled π-conjugated macromolecular architectures — A soft solution process based on Schiff base coupling

Abstract: Two-dimensional supramolecular covalent macromolecular architectures were visualized directly by in-situ scanning tunneling microcopy and colorful -conjugated nanofilms with unique mesostructures formed spontaneously on hydrophobic substrates from aqueous solutions in the presence of simple aromatic building block molecules under ambient conditions. We thus report the results of surface-mediated polycondensation and chemical liquid deposition. The Schiff base coupling reaction applied for this soft solution p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 68 publications
2
8
0
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 Schiff-bases are obtained in a two-step reaction involving complementary functionalities, amino and aldehyde (Scheme 1a). [28][29] This type of surface-confined condensation has been studied in either organic solvents [30][31][32][33][34][35] or aqueous solution: [36][37][38][39][40] in the second case the reactivity is known to be pH-dependent, offering a control on the reaction evolution. At low pH values the majority of the amino groups are in ammonium form (-NH 3 + ) and they are prevented to react with the aldehydes; by increasing the pH, the ammonium ions are deprotonated (to -NH 2 ) and can react forming Schiffbases (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 Schiff-bases are obtained in a two-step reaction involving complementary functionalities, amino and aldehyde (Scheme 1a). [28][29] This type of surface-confined condensation has been studied in either organic solvents [30][31][32][33][34][35] or aqueous solution: [36][37][38][39][40] in the second case the reactivity is known to be pH-dependent, offering a control on the reaction evolution. At low pH values the majority of the amino groups are in ammonium form (-NH 3 + ) and they are prevented to react with the aldehydes; by increasing the pH, the ammonium ions are deprotonated (to -NH 2 ) and can react forming Schiffbases (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…One of the proposed polymerization methods at the solid–liquid interface, easy and of low cost, utilizes the formation of Schiff-base functionalities in a condensation polymerization approach. Schiff bases are obtained in a two-step reaction involving complementary functionalities, amino and aldehyde (Scheme a). , This type of surface-confined condensation has been studied in either organic solvents or aqueous solution: in the second case the reactivity is known to be pH-dependent, offering a control on the reaction evolution. At low pH values the majority of the amino groups are in ammonium form (−NH 3 + ) and they are prevented to react with the aldehydes; by increase of the pH, the ammonium ions are deprotonated (to −NH 2 ) and can react forming Schiff bases (i.e., imines) through nucleophilic addition at the aldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we demonstrate the versatility of the presented SAMPA strategy for the fabrication of 2D nano‐architectures, by further increasing the number of plugs on each module A. Because of relatively weak interactions, [ 14 ] such as van der Waals interactions, hydrogen bonds, [ 15 ] and π stacking, [ 16 ] substrate‐supported self‐assembly is commonly necessary for the fabrication of 2D DNA lattices. Hence, we employed mica‐supported self‐assembly to facilitate the fabrication of 2D nano‐architectures.…”
Section: Resultsmentioning
confidence: 99%
“…Substrate-supported self-assembly is commonly achieved via relatively weak interactions 28 , such as van der Waals interactions, hydrogen bonds 39 40 41 and π stacking 42 . As an assembly unit for 2D lattices, we first employed a twist-corrected cross-shaped DNA origami with blunt ends ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The alternative approach is surface-diffusion-mediated self-assembly at the liquid–solid interface 25 26 27 . Success in this approach requires a weak adsorption condition that allows molecular mobility on the surface and/or a dynamic adsorption–desorption equilibrium 28 . Rafat et al 26 recently demonstrated a mica-surface-assisted assembly of DNA origami structures by controlling the surface mobility of the origami units via the addition of Na + ions.…”
mentioning
confidence: 99%